Sociology of Rationalism II: Disenchantment of the World and the Human Factor of Capitalism - Norkus, Zenonas (Problemos, 1990)
In Max Weber’s sociology of culture two possible solutions of the main problem of religion (endowing undeserved suffering with a sense) are distinguished – the Western one and the Eastern one. The most consistent Western-style solution of the problem (represented by Calvinism) imparts the most favourable conditions for the solution of the main economic problem (optimal allocation of resources under the circumstances of scarceness). The solution has given rise to the Western modem secular culture. In the culture religion loses its past dominant role.